Enfermedades Asociadas a las Actividades Agropecuarias: Análisis Geoespacial en San Isidro, Manabí-Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2024)
The population engaged in agricultural activity is particularly vulnerable to diseases due to acombination of factors associated with their work environment. The present research aims toidentify diseases associated with agricultural activity in the San Isidro parish of the provinceof Manabí, Ecuador. A sample of 92 families was taken, where the data was collected throughdocument review, interviews, surveys and direct observation, and analysis using Microsoft Exceland ArcGIS to obtain descriptive and cartographic results. The San Isidro parish has an area of277.95 km², where 89.73% of families are mainly engaged in agricultural activities and 7.34%in forestry activities. In this rural area, it was highlighted that there is a prevalence of primarylevel education with 60.29% of the population, of which 71.56% are economically active. In termsof health, 81.52% have peasant insurance, but only 17.39% are retired; consequently, 98.91% ofproducers have suffered some illness or parenteral injury due to their daily activities and only79.35% go to the nearest health center; the most common illness is influenza in the areas closestto the parish capital, followed by spinal problems that affect 42.39% of the population. With this,the research contributes to understanding health in agricultural environments to establish publicpolicies adapted to the needs of the parish, promoting its sustainability and integral development.
Keywords: agriculture; distribution of diseases; map; labor risks; occupational health